Success Factors in Implementing Tourist Information Service Innovations by Yogyakarta City Tourism Office - Moktika Sitoresmi; Bambang Utoyo S; Rahayu Sulistiowati (Magister Ilmu Pemerintahan FISIP Universitas Mulawaraman, 2025)
Public service innovation is one of the important strategies in improving the quality of tourism services, especially in responding to tourists' information needs in a fast, accurate, and accessible manner. This article analyzes the factors that drive the success of Tourist Information Service (TIS) innovation in Yogyakarta City by focusing on two main aspects: strategic location placement and the quality of human resources involved. This research uses a qualitative approach with data collection methods through in-depth interviews with informants from the Tourism Office, Indonesian Guides Association (HPI), Dimas Diajeng, and Saka Pariwisata. The results showed that the presence of TIS posts in Plaza Malioboro and Kilometer Zero Point succeeded in reaching tourists directly and spontaneously, strengthening the visibility and presence of government services in public spaces. On the other hand, the involvement of professional and culturally representative human resources is able to create a humanist and adaptive service experience. These findings are linked to the Diffusion of Innovation and Public Value Management theories, which emphasize the important role of change agents and collaborative value in the success of policy innovation. This article recommends the need to strengthen the HR training system, integrate information technology, and develop a service evaluation system as future policy directions. The limitation of the study lies in the narrow scope of variables, so a more comprehensive follow-up study is needed.